Influence of cooling rate on the Fe intermetallic formation in an AA6063 Al alloy - Verma, A; Kumar, S; Grant, P; O'Reilly, K (2013)
The influence of cooling rate during solidification on the three dimensional (3D) morphology of iron (Fe) bearing intermetallics in an AA6063 aluminium (Al) alloy has been investigated. Three dimensional quantitative and qualitative analyses were carried out on intermetallic particles extracted by dissolving the Al matrix. At slow cooling rate, the intermetallic particles were coarser (33 μm) and highly interconnected (113 μm) and their size and morphology was dependent on the grain/dendrite arm size of the primary Al. β-AlFeSi was the dominant (70%) intermetallic phase at low cooling rate (1.1 K/s) whereas αc-AlFeSi was more predominant (80%) at high cooling rate (16.6 K/s). © 2012 Elsevier B.V. All rights reserved.